Blood-sparing removal technique of extracorporeal membrane oxygenation circuit in a Jehovah Witness patient: Case report. Issue 31 (August 2019) - Park, Sang Min; Lee, Bom; Kim, Christopher Y.
Abstract: Rationale: Percutaneous cardiopulmonary support (PCPS) using extracorporeal membrane oxygenation (ECMO) is widely used in the critical patients with cardiopulmonary collapse. It is a representative blood-consuming procedure. In limited situations in which the option of blood transfusion is unavailable, there is no general agreement as to whether ECMO is contraindicated. Patient concerns: A 61-year-old male Jehovah Witness with acute respiratory collapse and loss of consciousness was rushed to our emergency room. Throughout his hospital course, the patient's family refused any type of blood transfusion even at the risk of death. Diagnosis: The clinical situations were secondary to a massive pulmonary thromboembolism Interventions: The patient underwent veno-venous ECMO via both femoral veins. The patient was recovered by intensive medical care although the level of hemoglobin (Hb) and hematocrit (Hct) was gradually decreased from 15.8 g/dl and 46.8% to 11.7 g/dl and 36.5%, respectively. Outcomes: On hospital day 3, ECMO was successfully removed using a blood-sparing ECMO removal technique involving the recycling of blood within the circuit by continuous saline infusion. There was no significant change in level of Hb/Hct and hemodynamic profile. At 2 days after ECMO removal, the level of Hb/Hct was elevated up to 9.2 g/dl and 30.0%, respectively without any transfusion. Lessons: Our blood-sparing removal technique of ECMO appears to be feasible and led to no significant adverse impact on hemodynamic status. The technique might be helpful for critical patients who cannot receive blood transfusion due to any cause.